1994
DOI: 10.1007/bf00044684
|View full text |Cite
|
Sign up to set email alerts
|

Solar-tracking leaf movements in velvetleaf (Abutilon theophrasti)

Abstract: Leaves of velvetleaf (Abutilon theophrasti) exhibited solar-tracking movements in several experiments using different cultural conditions near Ames, IA, U.S.A. Freely moving leaves maintained a smaller angle between the normal to the leaf and the sun's rays than did leaves fixed in one position in both greenhouse and field experiments. Freely moving leaves had higher total daily carbon gain, transpiration, and water use efficiency than leaves fixed in a horizontal position. Leaves on different sides of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…This could contribute to higher photochemical performance and better capability to use high-intensity light. Similar conclusions have been also reached in some previous studies (Ehleringer and Forseth 1980, Jurik and Akey 1994, Zhang et al 2009. The plants benefited from diaheliotropic movement to increase the potential photosynthesis as more light energy became available.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This could contribute to higher photochemical performance and better capability to use high-intensity light. Similar conclusions have been also reached in some previous studies (Ehleringer and Forseth 1980, Jurik and Akey 1994, Zhang et al 2009. The plants benefited from diaheliotropic movement to increase the potential photosynthesis as more light energy became available.…”
Section: Discussionsupporting
confidence: 88%
“…Diaheliotropism and paraheliotropism are two types of heliotropism that have been observed in many studies (Smith 1984, Koller 1986, 1990Rosa and Forseth 1995, Bielenberg et al 2003, Pastenes et al 2005, Arena et al 2008. Some previous studies have demonstrated that plants can improve their photosynthetic performance, promote carbon assimilation and water-use efficiency, and prevent light overload and blade overheating by heliotropic leaf movement (Jurik and Akey 1994, Caldas et al 1997, Bielenberg et al 2003, Liu et al 2003, Pastenes et al 2005, Arena et al 2008, Zhang et al 2009, Habermann et al 2011.…”
Section: Introductionmentioning
confidence: 98%
“…Velvetleaf exhibits solar-tracking leaf movements that maintain leaf blade angles near perpendicular to the sun (diaheliotropism). Solartracking leaves are predicted to have an assimilatory advantage over nontracking leaves (Jurik and Akey 1994). However, this is true only at low LAI values where self-shading is minimal (Gutschick 1991).…”
mentioning
confidence: 99%
“…However, this is true only at low LAI values where self-shading is minimal (Gutschick 1991). Jurik and Akey (1994) concluded that the significance of solar tracking in competitive interactions would depend on whether the tracking ability is maintained under shaded conditions.…”
mentioning
confidence: 99%
“…Utvrđeno je da ona "pravi" pokrete indukovane svetlošću koji postavljaju lisnu ploču pod uglom od skoro 90° u odnosu na upad sunčevih zraka, što je poznato kao diaheliotropizam. Dakle, biljke čiji listovi su skloni fototaksijama imaju prednost pri asimilaciji i iskorišćavanju svetlosti u odnosu na one koji nemaju to svojstvo (Jurik and Akey, 1994). Međutim, to važi samo pri niskim vrednostima indeksa lisne površine, kada je samozasenjivanje minimalno (Gutschick, 1991).…”
Section: Kompetitivnostunclassified